The Impact of Mortality Salience on Purchase Intention and Creativity Evaluation on Products During COVID-19 Pandemic - Zu, Chong; Zhou, Xiang; Cui, Yu-Xin; Liu, Yan-Fang; Hu, Yue-Xin; Li, Dong-Qi; Zeng, Hui (Frontiers in Psychology, 2021)
In the environment of COVID-19, people are faced with mortality salience and socioeconomic crisis. According to the Terror Management Theory, the mortality salience would lead to particular consumption attitudes and behaviors caused by the self-esteem and cultural worldview defense. The creativity as a potential value of products needs to be examined to explore how the mortality salience changed the creativity evaluation of three types of products categorized into normal, renovative, and innovative products, based on the degree of originality (Zhang et al., 2019). Two experiments are conducted to examine (1) the mortality salience effect on the creativity and purchase intention evaluation; (2) both mortality salience and country-of-origin effect on the evaluations. The results show that usefulness and purchase intention are affected by both effects, and the novelty is mainly affected by mortality salience.